Promoting and Protecting Apologetic Discourse through Law: A Global Survey and Critique of Apology Legislation - John Charles Kleefeld (Oñati Socio-Legal Series)
The year 2016 was a milestone for the law-and-apology field, marking the thirtieth anniversary of the first general law aimed at enabling apologies for civil wrongs, introduced in Massachusetts in 1986, as well as the tenth anniversary of the Apology Act, enacted in British Columbia in 2006. The Apology Act seeks to promote apologies and apologetic discourse as an important form of out-of-court dispute resolution, chiefly by making apologetic statements inadmissible for proving liability in civil wrongs. It has served as a benchmark from which subsequent law reform efforts in Canada and abroad have been measured. In 2017, that benchmark was passed with the enactment in Hong Kong of the most ambitious apology law yet, which privileges not only statements of remorse, but also statements of facts embedded in apologies. This article summarises global apology legislation and court decisions to date. Part I considers each major jurisdiction, starting with the USA and concluding with Hong Kong. Part II draws some conclusions about where we have been and where we are going in our efforts to promote or protect apologetic discourse, including recommendations on interpreting existing laws and on drafting or redrafting apology legislation.